2008
DOI: 10.1590/s1806-37132008001100016
|View full text |Cite
|
Sign up to set email alerts
|

Nocardiose pulmonar em portador de doença pulmonar obstrutiva crônica e bronquiectasias

Abstract: We report the case of a patient with chronic obstructive pulmonary disease and bronchiectasis, chronically using corticosteroids, who acquired pulmonary nocardiosis, which presented as multiple cavitated nodules. The principal symptoms were fever, dyspnea and productive cough with purulent sputum. Chest X-ray and computed tomography of the chest revealed nodules, some of which were cavitated, in both lungs. Sputum smear microscopy and culture revealed the presence of Nocardia spp. The patient was treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Pulmonary nocardiosis is a rare thoracic infection predominantly affecting immunocompromised hosts 8 The traditional risk factors for PN include long-term steroid therapy, malignancy, chemotherapy and HIV infection 11 However, one-third of cases reportedly occur in immunocompetent patients 12 There is increasing recognition that COPD is a risk factor for PN 13 Data are mostly from case reports and small series, given the rarity of PN. 3,4,1416 Notably, several of these cases have COPD associated with bronchiectasis and this is an important but under-recognized risk-factor for PN as well.3,13 In our series, bronchiectasis was the most common underlying CPD. No clustering of cases was noted and only five of the 22 cases were diagnosed and managed in the outpatient non-CF bronchiectasis clinic.…”
Section: Discussionmentioning
confidence: 57%
“…Pulmonary nocardiosis is a rare thoracic infection predominantly affecting immunocompromised hosts 8 The traditional risk factors for PN include long-term steroid therapy, malignancy, chemotherapy and HIV infection 11 However, one-third of cases reportedly occur in immunocompetent patients 12 There is increasing recognition that COPD is a risk factor for PN 13 Data are mostly from case reports and small series, given the rarity of PN. 3,4,1416 Notably, several of these cases have COPD associated with bronchiectasis and this is an important but under-recognized risk-factor for PN as well.3,13 In our series, bronchiectasis was the most common underlying CPD. No clustering of cases was noted and only five of the 22 cases were diagnosed and managed in the outpatient non-CF bronchiectasis clinic.…”
Section: Discussionmentioning
confidence: 57%
“…Pulmonary nocardiosis is the most common manifestation of Nocardia infection. The estimated annual incidence of pulmonary nocardiosis in the United States is between 500 and 1000 cases [ 4 ]. The majority of patients have impaired cell-mediated immunity, including those with underlying malignancies and human immunodeficiency virus infection, solid-organ or hematopoietic stem cell transplant recipients, and those receiving long term corticosteroids and medications that suppress cell-mediated immunity [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…The disease of pulmonary nocardiasis is rarely seen. It was reported that there is an approximate incidence of 500 to 1000 cases annually in the US [ 1 ]. The Nocardia is a Gram-positive filamentous bacteria and in a group of actinomycetes that can cause opportunistic infection in immune-compromised patients [ 2 ].…”
Section: Introductionmentioning
confidence: 99%